Forts in Between: The Defense of Manila and Macao during the Iberian Union - Luengo, Pedro (Archīum Ateneo, 2022)
Early modern fortifications have usually been understood merely as functional defensive instruments, and therefore their cultural features are undervalued. Much has been written about them in eighteenth-century Southeast Asian ports, but not as much has been studied regarding structures constructed during the Iberian Union (1580–1640). While previous studies have explained them as European constructions, Chinese expertise on fortifications and native manpower in the Philippines might have likewise played a role. For this reason, I cross-examine the archival materials and the preserved remains of fortifications in China and the Philippines.KEYWORDS: HISTORY OF ARCHITECTURE • TECHNICAL DIALOGUE •CHINESE FORTIFICATIONS • ETHNOCENTRICITY • BUILDING TECHNIQUES